Identification and Characterization of a New Type of Holin-Endolysin Lysis Cassette in Acidovorax oryzae Phage AP1 - Muchen Zhang; Yanli Wang; Jie Chen; Xianxian Hong; Xinyan Xu; Zhifeng Wu; Temoor Ahmed; Belinda Loh; Sebastian Leptihn; Sabry Hassan; Mohamed M. Hassan; Guochang Sun; et al. (Viruses, 2022)
Phages utilize lysis systems to allow the release of newly assembled viral particles that kill the bacterial host. This is also the case for phage AP1, which infects the rice pathogen Acidovorax oryzae. However, how lysis occurs on a molecular level is currently unknown. We performed in silico bioinformatics analyses, which indicated that the lysis cassette contains a holin (HolAP) and endolysin (LysAP), which are encoded by two adjacent genes. Recombinant expression of LysAP caused Escherichia coli lysis, while HolAP arrested growth. Co-expression of both proteins resulted in enhanced lysis activity compared to the individual proteins alone. Interestingly, LysAP contains a C-terminal region transmembrane domain, which is different from most known endolysins where a N-terminal hydrophobic region is found, with the potential to insert into the membrane. We show that the C-terminal transmembrane domain is crucial for protein localization and bacterial lysis in phage AP1. Our study characterizes the new phage lysis cassette and the mechanism to induce cell disruption, giving new insight in the understanding of phage life cycles.